Predictors of labor satisfaction an subjective well-being of Health professionals - Laura Paris (Psicodebate, 2015)
The aim of this study was to analyze the predictors of job satisfaction and subjective well-being in health professionals. We worked with a sample of 99 nurses and 97 doctors from Rosario city (Argentina). The subjects completed a questionnaire of personal data, two scales developed for this study (Care Stressors, and Coping with Care Stress), Job Satisfaction Scale (Shouksmith, 1990), and Subjective Well-being Inventory (Nacpal & Shell, 1992). Number of weekly working hours, problem-solving coping, satisfaction with life, and some dimensions of well-being (such as correspondence between expectations and achievements, the adequate mental management, and emotional support of family group), emerged as the strongest predictors of work satisfaction. Differences in function of the profession showed that, the best predictors, among physicians, are family and organizational support, and coherence between expectations and achievements (regarding salaries and promotion opportunities). In contrast, among nurses, only highlighted the use of cooperative coping as an explanatory variable. In relation to subjective well-being, the results showed that the best predictors are the following: having children, working more hours per week, perceiving organizational justice, using problem-solving coping, and being satisfied with their development of skills and capacities. The only difference in function of the profession shows that nurses respond to stressors using emotional distance and recreational leisure more often than doctors do.